PDTM-22. A C19MC-LIN28A-MYCN ONCOGENIC CIRCUIT DRIVEN BY HIJACKED SUPER-ENHANCERS IS A DISTINCT THERAPEUTIC VULNERABILITY IN ETMRS – A LETHAL BRAIN TUMOR. (11th November 2019) - Mumal, Iqra; Sin-Chan, Patrick; Suwal, Tannu; Singh, Irtisha; Li, Xiao-Nan; Lin, Charles; Rich, Jeremy; Mack, Stephen; Huang, Annie
Abstract: Embryonal tumors with multi-layered rosettes (ETMR) are aggressive brain cancers with characteristic C19MC oncomiR amplification and enrichment of pluripotency factor LIN28A. Here we investigated C19MC oncogenic mechanisms and discovered a potent C19MC -LIN28A-MYCN circuitry driven by multiple regulatory loops and super-enhancers resulting from long-range MYCN DNA interactions and C19MC gene fusions. C19MC and LIN28A targets respectively converge on critical cell cycle tumor suppressors and neo-embryonic DNMT3A/B isoforms. We identify a MYCN driven, core transcriptional network, conserved in early neural stem cells, that is potently abrogated by treatment with bromodomain inhibitor JQ1, leading to ETMR cell death. Our collective data suggest C19MC oncomiRs drive a malignant primitive cell state in ETMRs via entrapment of an early neural lineage network, which represents a critical therapeutic vulnerability for this recalcitrant disease.